FAKTA CERITA DALAM NOVEL ANGKASA DAN 56 HARI KARYA DESTASHYA WDP - Mahyud Daud; Irianto Ibrahim; La Ode Sahidin (Jurnal Bastra (Bahasa dan Sastra), 2024)
The aim of this research is to find out the facts of the story in the novel Angkasa and 56 Days by Destashya WDP. The type of research used is library research. The research method is descriptive qualitative. The data are written documents in the form of words, sentences and paragraphs that express the facts of the story in the novel Angkasa and 56 Hari by Destashya WDP. The data sources are the novels studied, namely the novel Angkasa and 56 Days by Destashya WDP. The data collection techniques are literature and documentation. This analyzed using a structural approach. Based on the results of facts in the novels Angkasa and 56 Days by Destashya WDP, the following conclusions can be drawn: (1) The theme is the tortuous journey of the love story between Nadine and Angkasa. (2) The distribution used in the novel Angkasa and 56 Days by Destashya WDP uses a mixed distribution process. (3) There are 20 characters in the novel Angkasa and 56 Hari by Destashya WDP. (4) The setting inthe novel Angkasa and 56 Hari by Destashya WDP has three types of setting, place setting, time setting and social setting. (5) Description of the relationship between the characters and the plot, Angkasa and Nadine who dominate all the events in the story. (6) Description relationship between characters and the setting. The description characters is supported by the setting, namely, all information regarding: place, time and social setting where the actions occur in the novel.